Underdevelopment through isolationism? Dependency theory in retrospect - Hermann Sautter (Intereconomics, 1985)
Until the mid seventies the dependency theory could be relied upon to stimulate lively debate, but nowadays it seems to arouse little interest. There are several reasons for this, a fundamental one being the fact that many of the central tenets of dependency theory have since had to be qualified, to some extent as a result of empirical studies by the theory's proponents themselves. This article examines the modification of certain aspects of the theory, such as its claim to explain underdevelopment and its recommendations as to the development strategy to follow.
Keywords: 330; Development Theory